Molecular genetics of idiopathic pulmonary fibrosis - R. N. Mustafin (Вавиловский журнал генетики и селекции)
Idiopathic pulmonary fibrosis (IPF) is a severe progressive interstitial lung disease with a prevalence of 2 to 29 per 100,000 of the world’s population. Aging is a significant risk factor for IPF, and the mechanisms of aging (telomere depletion, genomic instability, mitochondrial dysfunction, loss of proteostasis) are involved in the pathogenesis of IPF. The pathogenesis of IPF consists of TGF-β activation, epithelial-mesenchymal transition, and SIRT7 expression decrease. Genetic studies have shown a role of mutations and polymorphisms in mucin genes (MUC5B), in the genes responsible for the integrity of telomeres (TERC, TERC, TINF2, DKC1, RTEL1, PARN), in surfactant-related genes (SFTPC, SFTPCA, SFTPA2, ABCA3, SP-A2), immune system genes (IL1RN, TOLLIP), and haplotypes of HLA genes (DRB1*15:01, DQB1*06:02) in IPF pathogenesis. The investigation of the influence of reversible epigenetic factors on the development of the disease, which can be corrected by targeted therapy, shows promise. Among them, an association of a number of specific microRNAs and long noncoding RNAs was revealed with IPF. Therefore, dysregulation of transposons, which serve as key sources of noncoding RNA and affect mechanisms of aging, may serve as a driver for IPF development. This is due to the fact that pathological activation of transposons leads to violation of the regulation of genes, in the epigenetic control of which microRNA originating from these transposons are involved (due to the complementarity of nucleotide sequences). Analysis of the MDTE database (miRNAs derived from Transposable Elements) allowed the detection of 12 different miRNAs derived in evolution from transposons and associated with IPF (miR-31, miR-302, miR-326, miR-335, miR-340, miR-374, miR-487, miR-493, miR-495, miR-630, miR-708, miR-1343). We described the relationship of transposons with TGF-β, sirtuins and telomeres, dysfunction of which is involved in the pathogenesis of IPF. New data on IPF epigenetic mechanisms can become the basis for improving results of targeted therapy of the disease using noncoding RNAs.